MEASURING QUALITATIVE RESPONSE OF THE MOST IMPORTANT FACTORS AFFECTING THE ECONOMIC EFFICIENCY OF RICE FARMS IN NAJAF GOVERNORATE SEASON 2017 - Al-Wasity, R. T.; Mahmood, Z. H.; Ali, S. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study aimed to estimate rice farms efficiency using qualitative response models. The survied field included three districts in Najaf (Al Mishkhab, Al Hirah, Al Manadhira) during agricultural season 2017, including a random sample of 80 farms, representing 7.5% of the total farms. To achieve the goals, analysis was divided into two stages, the first stage was measuring the economic efficiency according to entry guidance of rice farms, while the second stage involved the analysis of factors affecting the economic efficiency of rice farms using the binomial logistic regression model to obtain a mathematical relationship between the dependent variable (response variable), which represents the economic efficiency of rice farms and the independent variables represented by age, experience and education of the owners , geographical area and type of possession for the farms. DEAP software was used to estimate economic efficiency and SPSS software to analyze the logistic regression of the factors affecting economic efficiency. The results showed that the average economic efficiency according to the Economic efficiency was 66.7%, which means that rice farmers can obtain the same production using 66.7% of the total costs i.e. there is a 33% waste in economic resources in the research sample.The logistic regression results indicated that each of experience (more than 35 years), education (university degree) and farm area (greater than 15 dunums) had a significant effect on the efficiency of the rice crop farms.